Study of the Antidepressant Activity of 4-Phenyl-2-thioxo-benzo[4,5]thieno[2,3-d]pyrimidine Derivatives - Darias, Victoriano; Abdala, Susana; Martìn-Herrera, Domingo; Vega, Salvador (Arzneimittelforschung, 1999)
A series of 23 4-phenyl-2-thioxo-benzo[4,5]thieno[2,3-d]pyrimidine derivatives were tested for acute toxicity and antidepressant activity in mice. Eight of the 23 compounds tested clearly antagonised the tetrabenazine effects and four of them (5, 7, 19, 23) showed activity values ranging from 40 to 75%, close to those shown by imipramine and viloxazine, the drugs chosen as reference standards. Compounds 7, 19 and 23 were also notably effective in the Porsolt test, shortening the immobility period of mice by more than 20%. The values obtained were very close to those elicited by imipramine and viloxazine. The most effective compounds in these tests were found among those bearing a primary amine or a benzoylamino group at the position 3 of the thieno[2,3-d]pyrimidine general structure (7, 19 and 23). The substitution of the thioxocarbonyl group at position 2 by a methylmercapto substituent maintained the activity (23). Compounds 7, 19 and 23 were chosen as prototypes for the design of new molecules with better antidepressant activity. These compounds did not present the adverse anticholinergic effects found in most tricyclic antidepressant drugs.
Keywords: Antidepressants; 4-Phenyl-2-thioxo-benzo[4,5]thieno[2,3-d]pyrimidines, antidepressant activity, mouse